Reforma al código de la niñez y la adolescencia, que sancione a la madre que no concurra a la realización del examen comparativo de los patrones de bandas o secuencias de ácido desoxirribonucleico ADN. - Sotomayor Torres, Gabriel Alexis (2012)
This research includes a study on the Code of Children and Adolescents with the project by bringing a legal proposal to rectify the legal precepts of the trial of the examination banding patterns or sequences of deoxyribonucleic acid (DNA) in As for the sanctions to have the defendant against the sanctions is not the plaintiff, which violate constitutional rights. With this research succeeds in establishing a legal alternative, legal and social legislation to improve Ecuadorian you have to see the trials of foods with a DNA test, and expose doctrinal character arguments to support the proposal legal, and , thus optimizing the administration and enforcement of the Code in question. The importance and implications of legal problems, about which there is no penalty for the mother who does not attend to the realization of comparative examination of the banding patterns or sequences of deoxyribonucleic acid (DNA) carries a very serious problem, since when there loopholes in our legislation as this creates problems in our environment, because there is often times unscrupulous people that all they want is a gain and not the interests of the child as the Code of Childhood and the Adolescence stipulated, with this we realize that there is no equality before the law and the Constitution and therefore it has a legal problem that needs analysis for their understanding. This research work, I present a budget that comes from intellectual effort, where guidelines are scientific and methodological research plays as a whole, on the formula to reform the Code of Childhood and the Adolescence, a provision to punish the plaintiff is not present comparative examination of bands or sequences of deoxyribonucleic acid (DNA), which reduces food trials raised in bad faith